Validation of a method for quantification of bisphenols and phthalate metabolites in post-mortem human brain tissue - Ian Zammit; Ayomi Jayarathne; Emerson Aldridge; Eurwin Suryana; Timothy A. Couttas; Geoff Eagleham; Chun-Yin (Julia) Lin; Claire E. Shepherd; Jochen F. Mueller; Christos Symeonides; Sarah Dunlop; Xianyu Wang (Analytica Chimica Acta, 2026)

Impact of nano zero valent iron dosing on biotransformation and adsorption of 20 biomarkers in sewers - Jianan Ren; Xiaotong Cen; Jiaying Li; Pritesh Prasad; Jiuling Li; Min Zheng; Adrian Covaci; Jochen F. Mueller; Phong K. Thai (Water Research, 2026)

Predictors of bisphenol A exposure in pregnant women of the Barwon Infant Study - Eva J. Sugeng; Sarah Thomson; James Hedley; Martin O’Hely; Christos Symeonides; Samantha L. Dawson; Luba Sominsky; Mimi L.K. Tang; Richard Saffery; Kristie Thompson; Jochen F. Mueller; Anne-Louise Ponsonby (Toxicology Letters, 2026)

Monitoring ketamine use and evaluating its persistence across 106 wastewater treatment plants in Australia - Zeyang Zhao; Rory Verhagen; Jake W. O’Brien; Benjamin J. Tscharke; Jinglong Li; Zhe Wang; Qiuda Zheng; Emma L. Keller; Jochen F. Mueller; Phong K. Thai (Journal of Water Process Engineering, 2026)

Chemical profiling of industry wastewaters to identify industry sources of contaminants - Chantal A. Keane; Rory Verhagen; Jochen F. Mueller; Jake W. O’Brien; Ryan Shiels; Jiaying Li (Water Research, 2026)

Nontarget GC-ECNI-Orbitrap-HRMS screening and evaluation method used to identify polyhalogenated compounds extracted from two passive air samplers deployed at marine islands in Australia - Sina Schweizer; Göksu Korkmaz; Jakob Hauns; Alexander Schächtele; Xianyu Wang; Chris Paxman; Jochen Mueller; Walter Vetter (Science of The Total Environment, 2026)

Deconjugation enzymes - pitfalls, contamination risks, and practical insights from human biomonitoring of bisphenols, phthalates, and oxidative stress markers - Ian Zammit; Yuya Cheng; Daniel Bury; Xianyu Wang; Jochen F. Mueller; Holger M. Koch (International Journal of Hygiene and Environmental Health, 2026)

Wastewater analysis as a global toxicovigilance tool for the monitoring of new psychoactive substances - Dhayaalini Nadarajan; Maria Laimou-Geraniou; Andrew Chappell; Christine Baduel; Lubertus Bijlsma; Tim Boogaerts; Daniel A. Burgard; Sara Castiglioni; Nicola Ceolotto; Erin M. Driver; Fernando Fabriz Sodre; Despo Fatta Kassinos; et al. (Water Research, 2026)

The natural product 2,4,6-tribromoanisole is the predominant polyhalogenated compound in representative Australian passive air samples - Sina Schweizer; Xianyu Wang; Chris Paxman; Jochen F. Mueller; Walter Vetter (Environmental Monitoring and Assessment, 2025)
Passive air samplers are well-suited for monitoring persistent organic pollutants (POPs) in ambient air. While the presence of POPs had been documented in Australian air, no data existed on structurally similar, halogenated natural products (HNPs), although these were frequently found in marine biota samples from Australia at levels exceeding those of anthropogenic POPs. This study reports quantitative data of the HNP 2,4,6-tribromoanisole (2,4,6-TBA) along with three POPs (polychlorinated biphenyls (PCBs) 153 and 138 as well as hexachlorobenzene (HCB)) in six selected passive air samples from different Australian regions (islands, coastal cities, and inland). For the most abundant HNP, 2,4,6-TBA, time-averaged concentrations for one year were determined at up to 420 pg/m 3 (One Tree Island), indicating its predominant natural production in the Great Barrier Reef (GBR). High concentrations of 2,4,6-TBA (17 pg/m 3 ), even in the remote inland sample (~ 800 km from the sea), led to the conclusion that the marine-derived 2,4,6-TBA was transported over long distances in air and can be found ubiquitously in Australian air. Even in the coastal cities of Brisbane and Darwin, 2,4,6-TBA levels were comparable to those of the PCBs. The HNP 2,3,3',4,4',5,5'-heptachloro-1'-methyl-1,2'-bipyrrole (Q1) was also detected in air from two islands. Its presence in air from One Tree Island was in line with expectations, given the high levels in marine mammal samples from the GBR. In direct comparison, the ~15 times higher ratio of Q1/2,4,6-TBA in air from Phillip Island indicated Q1 could be even more abundant in this marine region than in the GBR.

Identifying Populations with Elevated PFAS Exposure by Targeted Serum Sample Pooling - Sandra Nilsson; Jennifer Bräunig; Ava Mueller; Nis-Julius Sontag; Daman Langguth; Carl Kennedy; Peter Hobson; Kevin V. Thomas; Jochen F. Mueller; Leisa-Maree Toms (Exposure and Health, 2025)
Per- and polyfluoroalkyl substances (PFAS) are a focus of biomonitoring studies globally. In Australia, population PFAS serum concentrations have been determined since 2002 using pooled de-identified serum samples ( n = 4800) collected from the population bi-annually, as a component of the Australian Human Biomonitoring (HBM) project. Locations of environmental PFAS contamination (‘PFAS hotspots’) are known to exist in Australia, but the extent of human exposure at many of these hotspots remains unknown. This study assesses if systematic use of geographical pooling of surplus pathology samples can be effective to identify if elevated PFAS exposure has occurred in populations residing near ‘PFAS hotspots’. De-identified surplus pathology serum samples ( n > 1800) were obtained and pooled from postcodes near three ‘PFAS hotspots’. Samples were analyzed for PFAS and compared with the Australian HBM project. Selected PFAS were consistently higher compared to the Australian HBM project in pools from two of the three ‘PFAS hotspots’, suggesting that these populations may have experienced elevated exposure to PFAS. This study demonstrates that targeted serum pooling can be an effective tool for determining indications of population exposure to persistent chemicals in communities at risk. The technique has the potential to be used for rapid surveillance and as a trigger for further investigations of populations in proximity to sites with known contamination. Graphical Abstract

Utilizing national wastewater and sales data to derive and validate the correction factors of five common antidepressants for wastewater-based epidemiology - Zeyang Zhao; Jingyi Yuan; Qiuda Zheng; Benjamin J. Tscharke; Tim Boogaerts; Zhe Wang; Shuo Chen; Jake W. O'Brien; Alexander L.N. van Nuijs; Adrian Covaci; Jochen Mueller; Phong K. Thai (Water Research, 2025)

Organic cropping systems alter metabolic potential and carbon, nitrogen and phosphorus cycling capacity of soil microbial communities - Hans-Martin Krause; Ralf C. Mueller; Martina Lori; Jochen Mayer; Paul Mäder; Martin Hartmann (Soil Biology and Biochemistry, 2025)

Serum concentrations of PFAS across Australian States and Territories - Sandra Nilsson; Nathaniel Kucharski; Julia Orr; Jennifer Bräunig; Kristie Thompson; Olivier Jolliet; Daman Langguth; Carl Kennedy; Peter Hobson; Kevin V. Thomas; Jochen F. Mueller; Leisa-Maree Toms (International Journal of Hygiene and Environmental Health, 2025)

Occurrence and fate of glyphosate and AMPA in wastewater treatment plants in Australia - Garth Campbell; Ben J. Tscharke; Pritesh Prasad; Emma R. Knight; Tim Reeks; Aiko Jackson; Kevin V. Thomas; Jochen F. Mueller; Sarit L. Kaserzon (Science of The Total Environment, 2025)

Spatial variations in per- and polyfluoroalkyl substance concentrations in pooled sera from inland, coastal, and island populations - Julia J. Orr; Leisa-Maree Toms; Peter Hobson; Carl Kennedy; Daman Langguth; Nathaniel Kucharski; Adriana Santivanez Olazo; Jochen F. Mueller; Sandra Nilsson (Environmental Research, 2025)

Temporal trends of per- and polyfluoroalkyl substances concentrations: Insights from Australian human biomonitoring 2002–2021 and the U.S. NHANES programs 2003–2018 - Grechel Taucare; Gary Chan; Sandra Nilsson; Leisa-Maree L. Toms; Xingyue Zhang; Jochen F. Mueller; Olivier Jolliet (Environmental Research, 2024)

Metabolic changes associated with PFAS exposure in firefighters: A pilot study - Anna Rotander; Maria Jose Gomez Ramos; Jochen F. Mueller; Leisa-Maree Toms; Tuulia Hyötyläinen (Science of The Total Environment, 2024)

Per- and polyfluoroalkyl substances (PFAS) in floor dust from different indoor environments in Australia: Levels, variation, and human exposure risks - Zongrui Li; Zubaria Ishaq; Chang He; Andrew P.W. Banks; Jennifer Bräunig; Phong K. Thai; Ayomi Jayarathne; Jochen F. Mueller; Xianyu Wang (Chemosphere, 2024)

Assessing daily patterns in stimulant use during the COVID-19 pandemic in Melbourne, Australia using wastewater analysis - Shuo Chen; Richard Bade; Ben Tscharke; Wayne Hall; Phong Thai; Chang He; Fahad Ahmed; Qiuda Zheng; Phil M. Choi; Jake W. O’Brien; Jochen F. Mueller (Journal of Hazardous Materials, 2024)

The complex effect of dissolved organic carbon on desorption of per- and poly-fluoroalkyl substances from soil under alkaline conditions - Shervin Kabiri; Ehsan Tavakkoli; Divina A. Navarro; Fien Degryse; Charles Grimison; Christopher P. Higgins; Jochen F. Mueller; Rai S. Kookana; Michael J. McLaughlin (Environmental Pollution, 2024)

Application of design of experiment for quantification of 71 new psychoactive substances in influent wastewater - Dhayaalini Nadarajan; Jake O'Brien; Sarah Cresswell; Ben Kele; Jochen Mueller; Richard Bade (Analytica Chimica Acta, 2024)

Review on Methods for Assessing and Predicting Leaching of PFAS from Solid Matrices - Divina A. Navarro; Shervin S. Kabiri; Karl Bowles; Emma R. Knight; Jennifer Braeunig; Prashant Srivastava; Naomi J. Boxall; Grant Douglas; Jochen Mueller; Mike J. McLaughlin; Mike Williams; Rai S. Kookana (Current Pollution Reports, 2024)
Purpose of Review Per- and poly-fluoroalkyl substances (PFAS) are prevalent environmental contaminants detected in materials such as soils, biosolids, and wastes. Understanding PFAS leaching is crucial for assessing risks associated with leaving impacted material in place, reuse, or disposal. However, there is limited guidance on laboratory methods to measure extent and rate of leaching. This review aims to identify the best methods for assessing PFAS leaching that are reflective of relevant release scenarios. Recent Findings Various methods have been applied to assess PFAS leaching from contaminated materials. The most common are batch leaching methods that simulate particular conditions (e.g. rainfall, landfill), with the intention of providing conservative estimates (worst-case scenarios) of cumulative PFAS release over time. Columns, static leaching, and rainfall simulators are also used to simulate less aggressive field-like conditions. While less common, pan and suction lysimeters have been used to measure PFAS leaching in situ. Most methods use saturated conditions that do not account for the possible influence of air–water interface accumulation and wetting–drying cycles on leaching. A notable gap is the scarcity of data benchmarking laboratory-leached concentrations with real-world PFAS concentrations. Establishing this relationship is crucial for reliable laboratory protocols. Summary This article reviews methods for estimating leaching of PFAS from contaminated materials. Given the variety of methods, selecting those that best simulate assessment objectives is essential. Specific scenarios requiring PFAS leaching assessment, such as leaving materials in place, reuse, and disposal, are discussed. The knowledge gaps presented could be used to improve existing leaching methods for better predictions and understanding of PFAS leachability. Graphical Abstract

Nationwide occurrence and discharge mass load of per- and polyfluoroalkyl substances in effluent and biosolids: A snapshot from 75 wastewater treatment plants across Australia - Hue T. Nguyen; Phong K. Thai; Sarit L. Kaserzon; Jake W. O'Brien; Jochen F. Mueller (Journal of Hazardous Materials, 2024)

Workflow to facilitate the detection of new psychoactive substances and drugs of abuse in influent urban wastewater - Richard Bade; Denice van Herwerden; Nikolaos Rousis; Sangeet Adhikari; Darren Allen; Christine Baduel; Lubertus Bijlsma; Tim Boogaerts; Dan Burgard; Andrew Chappell; Erin M. Driver; Fernando Fabriz Sodre; et al. (Journal of Hazardous Materials, 2024)

Wastewater-based monitoring of the nitazene analogues: First detection of protonitazene in wastewater - Richard Bade; Dhayaalini Nadarajan; Erin M. Driver; Rolf U. Halden; Cobus Gerber; Alex Krotulski; Wayne Hall; Jochen F. Mueller (Science of The Total Environment, 2024)

Monitoring the use of novel psychoactive substances in Australia by wastewater-based epidemiology - Emma L. Jaunay; Richard Bade; Kara R. Paxton; Dhayaalini Nadarajan; Daniel C. Barry; Yuze Zhai; Benjamin J. Tscharke; Jake W. O'Brien; Jochen Mueller; Jason M. White; Bradley S. Simpson; Cobus Gerber (Science of The Total Environment, 2024)

Blueprint for the design, construction, and validation of a plastic and phthalate-minimised laboratory - Cassandra Rauert; Xianyu Wang; Nathan Charlton; Chun-Yin Lin; Cheng Tang; Ian Zammit; Ayomi Jayarathne; Christos Symeonides; Emily White; Michael Christensen; Valentina Ponomariova; Jochen F. Mueller; et al. (Journal of Hazardous Materials, 2024)

Distribution and release of PFAS from AFFF-impacted asphalt: How does it compare to concrete? - Yijing Li; Trent A. Key; Phong H.N. Vo; Scott Porman; Anita Thapalia; Jeffrey T. McDonough; Stephanie Fiorenza; Craig M. Barnes; Jochen F. Mueller; Phong K. Thai (Journal of Hazardous Materials, 2024)

Analysis of wastewater from 2013 to 2021 detected a recent increase in nicotine use in Queensland, Australia - Zhe Wang; Qiuda Zheng; Jake W. O'Brien; Benjamin J. Tscharke; Gary Chan; Kevin V. Thomas; Jochen F. Mueller; Phong K. Thai (Water Research, 2024)

In-sewer stability of 31 human health biomarkers and suitability for wastewater-based epidemiology - Jiaying Li; Phil M. Choi; Jianfa Gao; Jianan Ren; Jake W. O'Brien; Kevin V. Thomas; Jochen F. Mueller; Phong K. Thai; Guangming Jiang (Water Research, 2024)

Surface rupturing earthquakes along the eastern Rhine Graben Boundary Fault near Ettlingen-Oberweier (Germany) - Sara Pena-Castellnou; Jochen Hürtgen; Stéphane Baize; Frank Preusser; Daniela Mueller; Hervé Jomard; Edward M. Cushing; Thomas K. Rockwell; Gordon Seitz; Francesca R. Cinti; Joachim Ritter; Klaus Reicherter (Tectonophysics, 2023)

Spatial and temporal trends of 64 pesticides and their removal from Australian wastewater - Emma R. Knight; Rory Verhagen; Jochen F. Mueller; Ben J. Tscharke (Science of The Total Environment, 2023)

Exploring drug consumption patterns across varying levels of remoteness in Australia - Rory Verhagen; Sarit L. Kaserzon; Kevin V. Thomas; Jochen F. Mueller; Benjamin J. Tscharke (Science of The Total Environment, 2023)

Evaluation and identification of chemical migrants leached from baby food pouch packaging - Cheng Tang; María José Gómez Ramos; Amy Heffernan; Sarit Kaserzon; Cassandra Rauert; Chun-Yin Lin; Jochen F. Mueller; Xianyu Wang (Chemosphere, 2023)

Bisphenols and phthalates in Australian wastewater: A statistical approach for estimating contributions from diffuse and point sources - Belinda Moore; Chang He; Emma Knight; Jochen F. Mueller; Benjamin Tscharke (Water Research, 2023)

Direct injection liquid chromatography-tandem mass spectrometry as a sensitive and high-throughput method for the quantitative surveillance of antimicrobials in wastewater - Jinglong Li; Katja M. Shimko; Chang He; Brad Patterson; Richard Bade; Ryan Shiels; Jochen F. Mueller; Kevin V. Thomas; Jake W. O'Brien (Science of The Total Environment, 2023)

Monitoring medication and illicit drug consumption in a prison by wastewater-based epidemiology: Impact of COVID-19 restrictions - Zhe Wang; Jochen F. Mueller; Jake W. O'Brien; Jack Thompson; Benjamin J. Tscharke; Rory Verhagen; Qiuda Zheng; Jeremy Prichard; Wayne Hall; Keith Humphreys; Kevin V. Thomas; Phong K. Thai (Water Research, 2023)

Assessing the effects of COVID-19 restrictions on alcohol consumption in Melbourne, Australia using high-resolution wastewater sampling - Shuo Chen; Richard Bade; Ben Tscharke; Wayne Hall; Michael Livingston; Phong Thai; Chang He; Qiuda Zheng; Nick Crosbie; Jochen Mueller (Science of The Total Environment, 2023)

Estimation of per- and poly-fluoroalkyl substances mass loads in the Danube River using passive sampling - Carly Beggs; Rachel Mackie; Branislav Vrana; Roman Prokeš; Sara Ghorbani Gorji; Bastian Schulze; Kevin V. Thomas; Jochen F. Mueller; Sarit L. Kaserzon (Science of The Total Environment, 2023)

Physical and chemical properties of carbon-based sorbents that affect the removal of per- and polyfluoroalkyl substances from solution and soil - Shervin Kabiri; Divina A. Navarro; Suhair Ahmed Hamad; Charles Grimison; Christopher P. Higgins; Jochen F. Mueller; Rai S. Kookana; Michael J. McLaughlin (Science of The Total Environment, 2023)

Liver and cardiometabolic markers and conditions in a cross-sectional study of three Australian communities living with environmental per- and polyfluoroalkyl substances contamination - Nina Lazarevic; Kayla S. Smurthwaite; Catherine D'Este; Robyn M. Lucas; Bruce Armstrong; Archie CA. Clements; Susan M. Trevenar; Imogen Gad; Rose Hosking; Hsei Di Law; Jochen Mueller; Jennifer Bräunig; et al. (Environmental Research, 2023)

Wastewater-based epidemiology for the assessment of population exposure to chemicals: The need for integration with human biomonitoring for global One Health actions - Barbara Kasprzyk-Hordern; Frederic Béen; Lubertus Bijlsma; Werner Brack; Sara Castiglioni; Adrian Covaci; Bice S. Martincigh; Jochen F. Mueller; Alexander L.N. van Nuijs; Temilola Oluseyi; Kevin V. Thomas (Journal of Hazardous Materials, 2023)

First indication of perfluoroalkyl substances in human serum from Papua New Guinea - Hong T.M. Nguyen; Sandra Nilsson; Ava A.R. Mueller; Leisa-Maree Toms; Carl Kennedy; Daman Langguth; Peter Hobson; Jochen F. Mueller (Science of The Total Environment, 2023)

The efficacy of soil washing for the remediation of per- and poly-fluoroalkyl substances (PFASs) in the field - Charles Grimison; Emma R. Knight; Thi Minh Hong Nguyen; Nathan Nagle; Shervin Kabiri; Jennifer Bräunig; Divina A. Navarro; Rai S. Kookana; Christopher P. Higgins; Michael J. McLaughlin; Jochen F. Mueller (Journal of Hazardous Materials, 2023)

Detections of organophosphate and pyrethroid insecticide metabolites in urine and sweat obtained from women during infrared sauna and exercise: A pilot crossover study - Joy Hussain; Marc Cohen; Cindy J. O'Malley; Nitin Mantri; Yan Li; Jochen F. Mueller; Ronda Greaves; Xianyu Wang (International Journal of Hygiene and Environmental Health, 2023)

Longitudinal measurements of per- and poly-fluoroalkyl substances (PFAS) in archived human serum samples between 1975 and 1995 in Australia - Sandra Nilsson; Jennifer Bräunig; Renee N. Carey; Jennie Hui; Kayla Smurthwaite; Leisa-Maree Toms; Martyn D. Kirk; Jochen F. Mueller; Lin Fritschi (Journal of Hazardous Materials, 2023)

Corrigendum to “Simultaneous removal of micropollutants, antibiotic resistant bacteria, and antibiotic resistance genes using graphitic carbon nitride under simulated solar irradiation” [Chem. Eng. J. 433 (2022) 133839] - Jiexi Zhong; Yunus Ahmed; Gilda Carvalho; Zhiliang Wang; Lianzhou Wang; Jochen F. Mueller; Jianhua Guo (Chemical Engineering Journal, 2023)

The May 15, 2020 M 6.5 Monte Cristo Range, Nevada, earthquake: eyes in the sky, boots on the ground, and a chance for students to learn - Taha Sadeghi Chorsi; Jochen Braunmiller; Fanghui Deng; Nicholas Mueller; Scott Kerstetter; Robert J. Stern; Timothy H. Dixon (International Geology Review, 2022)

Journal Club - Andreas Seiffert-Störiko; Jörg Stülke; Victor Sourjik; Jonathan Wolf Mueller; Jürgen Lassak; Daniela Kruck; Katja Taute; Johannes Sander; Bettina Siebers; Jochen Graw (BIOspektrum, 2022)

Journal Club - Wolfgang Wohlleben; Jochen Graw; Roland Benz; Johannes Sander; Jonathan Wolf Mueller; Christoph von Ballmoos; Miriam Herbert; Daniela Kruck; Martin Thanbichler; Gottfried Wilharm; Kai Thormann; Thilo M. Fuchs; et al. (BIOspektrum, 2020)

Temporal profile of illicit drug consumption in Guangzhou, China monitored by wastewater-based epidemiology - Xiaohan Zhang; Riheng Huang; Ping Li; Yuan Ren; Jianfa Gao; Jochen F. Mueller; Phong K Thai (Environmental Science and Pollution Research, 2019)

Tsunami runup and tide-gauge observations from the 14 November 2016 M7.8 Kaikōura earthquake, New Zealand - William Power; Kate Clark; Darren N. King; Jose Borrero; Jamie Howarth; Emily M. Lane; Derek Goring; James Goff; Catherine Chagué-Goff; James Williams; Catherine Reid; Colin Whittaker; et al. (Pure and Applied Geophysics, 2017)

Enhanced aphid abundance in spring desynchronizes predator–prey and plant–microorganism interactions - Benjamin Fuchs; Tatjana Breuer; Simone Findling; Markus Krischke; Martin J. Mueller; Andrea Holzschuh; Jochen Krauss (Oecologia, 2017)

Peramine and Lolitrem B from Endophyte-Grass Associations Cascade Up the Food Chain - Benjamin Fuchs; Markus Krischke; Martin J. Mueller; Jochen Krauss (Journal of Chemical Ecology, 2013)

Growth under uncertainty: The influence of marine variability on early development of Galapagos sea lions - Birte Mueller; Ulrich Pörschmann; Jochen B. W. Wolf; Fritz Trillmich (Marine Mammal Science, 2011)
Development implies a change in allocation of resources from somatic growth to reproduction. In a highly variable environment, growth can vary from year to year thereby influencing the long‐term life history perspective. The Galapagos sea lion ( Zalophus wollebaeki ) lives in a highly unpredictable marine environment in which food abundance varies not only seasonally, but also annually due to El Niño. Galapagos sea lions are restricted to a patch of cold upwelling waters surrounding the archipelago and are closely tied to land as nursing females alternate between foraging at sea and nursing ashore. Therefore, their offspring are especially vulnerable to ocean warming causing reduced food abundance. We found a significant correlation between sea surface temperature (SST) and early growth: Both mass at birth and linear growth within the first 2 mo of life correlated negatively with SST. Absolute mass gain was higher for males, but both sexes gained equally 1.9% of birth mass per day. Until the age of 3 yr male and female juveniles showed similar growth to an asymptotic mass of 40 and 35 kg, respectively. As a consequence of the highly variable environment, the plasticity in growth strategy of Galapagos sea lion juveniles appears wider than that of all other sea lions allowing them to cope with poor conditions.

Male reproductive success and its behavioural correlates in a polygynous mammal, the Galápagos sea lion (Zalophus wollebaeki) - ULRICH PÖRSCHMANN; FRITZ TRILLMICH; BIRTE MUELLER; JOCHEN B. W. WOLF (Molecular Ecology, 2010)